Analysis of Adoption and Impact of Digital Business Models: a Qualitative Study of the Experience and View of Small and Medium Enterprises (SMEs) - Muhammad Ardiansyah (Journal Markcount Finance, 2024)
This study aims to analyze the adoption and impact of digital business models on small and medium enterprises (SMEs). This study uses a qualitative approach through in-depth interviews with owners and managers of SMEs that have adopted digital business models. The main objective of this study is to analyze the factors that influence the adoption of digital business models, as well as analyze the impact resulting from this adoption. The research was conducted by collecting data through structured in-depth interviews with owners and managers of SMEs representing various industrial sectors. The collected data were analyzed using a qualitative analysis approach by identifying the main themes that emerged from the interviews. The results of the study show that there are factors that influence the adoption of digital business models in SMEs, such as technology awareness, availability of resources, digital skills, and the regulatory environment. The adoption of digital business models has had a significant impact on SMEs, including increasing market access, increasing operational efficiency, expanding customer reach, and increasing competitiveness.